PENGARUH KOMPETENSI, MOTIVASI, DISIPLIN TERHADAP KINERJA GURU SD UPT KEDUNGWUNI - Pahroji, Pahroji (Students Journal of Economic and Management, 2012)
This study aimed to analyze the effect of teacher competence, motivation, and dicipliine to the performance of primary school teachers working in education and culcure Kedungwuni UPT Pekalongan. The research instrument used in this study qualify validity, a factor analysis. Because all the indicators in the research instruments have loading factors above 0,4; similarly KMO sample adequacy or condition is above 0,5. This study used a sample taken as a source of data and can reprseat the whole population, sample in this study using a random sample (random sampling) with sampling techniques using the formula of Taro Yamame or Sloving obtained a sample of 125 respondents form 266 population, hypothesis test used in this study is regression analysisi with t count, hypothesis testing is used t count frequency distribution test at a significant level (Î±) 5 %. Based on tthe above rresults can bbe summarized as follows: (1) the competence of teachers and signifcant negative effecct to the performance of teachers, (2) work motivation has positive and significant impact on teachers performance, (3) labor discipline and significant positive effect on teachers performance.. Keywords: teacher completence, motivation, dicipliine, and Â the performance